The Mustache: An Indispensable Element of Alevî-Bektashi Physical Folklore (Journal of Alevism-Bektashism Studies, 2025)
From the perspective of body folklore, this study aims to illuminate an area that has not been sufficiently studied to date by examining the historical, cultural, and symbolic meanings of the beard and mustache among Alevî-Bektashis within the Islamic belief system. Based on the understanding that the body is shaped by culture and makes culture visible, it is evident that the beard and mustache are forms of religious expression. Unlike Sunnite and Shiite traditions, the meanings carried by bodily symbols in Alevî-Bektashi communities reflect a unique belief and philosophy of life. Therefore, analyzing expressions such as beards and mustaches is extremely valuable and necessary for understanding Alevî-Bektashi culture. In Alevî-Bektashi communities, the beard and mustache have been considered indicators of secrecy, bâtıniness, resistance, and identity consciousness, and in this respect, they have been the carriers of both individual and social memory. The cutting or shaping of the beard and moustache has not only been limited to religious rituals, but has also become a symbol of religious devotion, mystical upbringing, and historical belonging. This study aims to contribute to both folklore and Islamic mysticism literature by revealing the historical, ritual, and cultural contexts of the beard and mustache within the scope of Alevî-Bektashi body folklore. The study is also important in demonstrating how the body functions as a language of belief, how cultural identities are embodied, and how these symbols evolve into a historical field of resistance. The document analysis method, a qualitative research approach, was employed in the study. Written, visual, and audio academic studies on beard and mustache culture were analyzed through content analysis and critical discourse analysis techniques. In addition, relevant visuals were added to the study to give a better idea of the subject.